A Congenital Peribronchial Myofibroblastic Tumor Detected in a Premature Infant at 28 Weeks but That Resolved in the Late Stage of Pregnancy: A Case Report. Issue 42 (October 2015) - Xia, Bo; Yu, Gang; Hong, Chun; Zhang, Lei; Tang, Jing; Liu, Cuifen
Abstract : Abstract: A congenital peribronchial myofibroblastic tumor (CPMT) is a rare benign tumor arising from the lungs. Although CPMT is a benign tumor, it is characterized by rapid growth, and is easily misdiagnosed during the prenatal period when the symptoms are nonspecific. The authors present a rare case of CPMT in a premature infant, which was detected at 28 weeks on ultrasonography (US) but resolved at a later stage of pregnancy. The knowledge concerning the diagnosis and management of CPMT is reviewed. Herein, the authors report of a 30-minute-old premature newborn infant in whom a pulmonary mass was discovered 1 month before delivery. Maternal prenatal US demonstrated a 0.8 × 1 cm well-defined oval-shaped mass in the left hemithorax in the 28th week of gestational age. The pulmonary mass, however, was not apparent on repeat US examination at 32 weeks. The child was delivered by cesarean section at 34 weeks estimated gestational age. Chest radiography and computed tomography revealed a mass-like lesion in the left lower pulmonary lobe. The chest computed tomography characteristics of the tumor included large size (4 cm), an irregular margin, and surrounding ground-glass opacity, which led to misdiagnosis as a malignant tumor. The patient underwent a left inferior lung lobectomy and was pathologically diagnosed with CPMT. He is currently alive 12-month postresection with no evidence of disease recurrence. The authors report this rare case of CPMT, which was detected at 28 weeks and resolved at a later stage of pregnancy. Congenital peribronchial myofibroblastic tumor is an uncommon benign tumor. Lobectomy or pneumonectomy is often required. The prognosis after surgery is good.